2016
DOI: 10.18632/oncotarget.13136
|View full text |Cite
|
Sign up to set email alerts
|

MiR-142 inhibits the development of cervical cancer by targeting HMGB1

Abstract: It has been reported that miRNAs is deregulated in diverse human cancers, involving human cervical cancer. However, the clinical significances and potential mechanisms of miR-142 in the development and progression of cervical cancer were not elucidated completely till now. In this study, we found that the expression of miR- 142 was obviously down-regulated in human cervical cancer tissues and a panel of cell lines. According to statistics, the expression of miR-142 was negatively related to advanced FIGO stage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 22 publications
3
18
1
Order By: Relevance
“…Furthermore, we show that our rat asthma models exhibited reduced miR-142 expression. Relatedly, Jiang et al reported that miR-142 was expressed at low levels in several cancer tissues and was associated with pathological indicators in cancer patients; miR-142 overexpression was also found to influence prostate cancer cell growth by targeting the androgen receptor [26]. However, few studies have investigated the dynamics of miR-142 expression or the mechanism by which miR-142 exerts its effects.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we show that our rat asthma models exhibited reduced miR-142 expression. Relatedly, Jiang et al reported that miR-142 was expressed at low levels in several cancer tissues and was associated with pathological indicators in cancer patients; miR-142 overexpression was also found to influence prostate cancer cell growth by targeting the androgen receptor [26]. However, few studies have investigated the dynamics of miR-142 expression or the mechanism by which miR-142 exerts its effects.…”
Section: Discussionmentioning
confidence: 99%
“…There is a reverse association between miR‐34a, miR‐1284and miR‐142 and HMBG1 expression. Therefore, downregulation of miR‐34a, miR‐1284and miR‐142 can enhance CC proliferation, invasion and inflammation by upregulating HMGB1 . HMGB1 expression is one cause of chemoresistance, so that miR‐1284 downregulation (a tumor suppressor in CC) increases the resistance of CC cells to cisplatin and inhibits apoptosis via HMGB1 upregulation .…”
Section: The Role and Function Of Micrornas In Cervical Cancer Inflammentioning
confidence: 99%
“…Therefore, downregulation of miR-34a, miR-1284and miR-142 can enhance CC proliferation, invasion and inflammation by upregulating HMGB1. [108][109][110] HMGB1 expression is one cause of chemoresistance, so that miR-1284 downregulation (a tumor suppressor in CC) increases the resistance of CC cells to cisplatin and inhibits apoptosis via HMGB1 upregulation. 109 HMGB1 plays a significant role in the lymphatic metastasis in CC patients, and it has been demonstrated that downregulation of miR-142 augments lymphatic metastasis in CC patients.…”
Section: Hpv and Inflammation In Cervical Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…miR‐142 was identified to dysregulated in different types of tumours. miR‐142 was up‐regulated in human breast cancer stem cells (BCSCs) as compared to the non‐tumorigenic breast cancer cells but obviously down‐regulated in human cervical cancer tissues and HCC tissues . But, to date, the courses of this dysregulation in HCC and related function have not fully understood.…”
Section: Introductionmentioning
confidence: 99%